PELATIHAN DAN PENDAMPINGAN PENULISAN KARYA ILMIAH BAGI GURU-GURU SMP DI SENTANI - Ida Mariati Hutabarat; Epiphani I.Y. Palit; Monika Gultom (JURNAL PENGABDIAN PAPUA, 2019)
Some of the problems faced by teachers in Sentani are the ability to write or express ideas in writing in general is still very low. Teachers are generally not used to writing. They lacked understanding of the rules of writing scientific papers and generally had no ideas to write. This is very related to the problem of lack of sources of information in the form of books and journals about education. Teachers have difficulty in searching references / libraries in various sources. As well as teachers experiencing obstacles in terms of sending publications. This service program aims to resolve the above problems through training activities in research methodology and mentoring to publish their work and direct the teacher to the journal to be addressed.  The method used for solutions to problems faced by teachers and to support the success of the program is in the form of lectures, question and answer, demonstrations and practice / writing. Participants who have participated in the training will immediately practice the results of the training they get and make scientific papers with the guidance of the trainers so that participants can make scientific papers well. Keywords: papers, teacher professional development, SMPN Sentani